Utilization of Weighted Moving Average for Decision Support Systems for Sales Services and Stock Management Case Study: Soes Merdeka Bread Shop - Ayu Setya Ningrum; Irwan A. Kautsar; Nuril Lutvi Azizah; Sukma Aji (Research Parks Publishers, 2026)
Business owners are leveraging the rapidly developing advancements in information technology to simplify sales and inventory management. Increasingly dynamic business competition demands that companies provide products at the right time and in the right quantities to meet consumer needs. Toko Roti Soes Merdeka, a MSME specializing in bread and cake sales, faces challenges in managing stock availability without causing excess or shortage of inventory. Based on these problems, the purpose of this study is to design a web-based decision support system using the Weighted Moving Average (WMA) method to forecast sales based on historical data collected from May 18–24, 2025. The WMA method assigns different weights to each period, resulting in more accurate predictions in determining stock requirements for the following period. The results show that the system developed is capable of assisting transaction recording, stock management, and presenting forecasting results automatically and in a structured manner, thereby supporting more effective and efficient decision-making.